2012
DOI: 10.1111/j.1749-7345.2012.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Juvenile Green Sea Urchins, Strongylocentrotus droebachiensis, Fed Formulated Feeds with Varying Protein Levels Compared with a Macroalgal Diet and a Commercial Abalone Feed

Abstract: The effects of varying protein and carbohydrate levels in prepared diets on the somatic growth of juvenile green sea urchins, Strongylocentrotus droebachiensis, were examined. Ten diets were tested on 600 hatchery reared urchins (mean start weight = 0.11 g) for 6 mo with three replicate groups per diet. Nine of the diets were prepared specifically for urchins and varied in protein (16–40% protein) and carbohydrate (29–49% carbohydrate) levels. The other two diets consisted of a commercially available abalone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…This is consistent with James et al (2007), who found that urchins with poor initial gonad quality benefited more from gonad conditioning than urchins with higher initial gonad quality. Improvement in gonad quality from an artificial diet contrasts with numerous studies where algal diets produced roe of better colour than artificial diets (Shpigel et al 2004, Phillips et al 2009, Eddy et al 2012, Cyrus et al 2013). However, gonad conditioning did not improve the overall gonad quality of urchins from Barren 1 (Fig.…”
Section: In-season Gonad Conditioningmentioning
confidence: 62%
“…This is consistent with James et al (2007), who found that urchins with poor initial gonad quality benefited more from gonad conditioning than urchins with higher initial gonad quality. Improvement in gonad quality from an artificial diet contrasts with numerous studies where algal diets produced roe of better colour than artificial diets (Shpigel et al 2004, Phillips et al 2009, Eddy et al 2012, Cyrus et al 2013). However, gonad conditioning did not improve the overall gonad quality of urchins from Barren 1 (Fig.…”
Section: In-season Gonad Conditioningmentioning
confidence: 62%
“…As nutritional requirements of adult L. variegatus may vary from those of juveniles, dietary requirements and efficiencies among marketable adults must also be evaluated at their respective size and/or age classes. Data reported by Eddy et al (2012) indicate that economic returns among other species of interest may vary from that of L. variegatus . Therefore, predictive modeling and economic analysis will be necessary for urchin species with life history and/or feeding strategies that differ from those of L. variegatus.…”
Section: Discussionmentioning
confidence: 99%
“…Dry matter production among adult L. variegatus increases with increasing level of dietary protein, but feed efficiency is correspondingly reduced (Hammer et al, 2012; Heflin et al, 2012). In contrast, wet weight gain among juvenile S. droebachiensis decreases with increasing level of dietary protein (Eddy et al, 2012), indicating that protein levels above ca. 20% may inhibit growth in this cold water species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Pearce et al . ; Kennedy, Robinson, Parsons & Castell ; Eddy, Brown, King, Watts & Lawrence ), compared with 40% protein for small M. franciscanus (McBride et al . ).…”
Section: Introductionmentioning
confidence: 99%